Stereotactic Radiotherapy for Parasagittal and Parafalcine Meningiomas: Patient Selection and Special Considerations - Pinzi V; Fariselli L; Marchetti M; Scorsetti M; Navarria P (Cancer Management and Research, 2019)
V Pinzi,1 L Fariselli,1 M Marchetti,1 M Scorsetti,2 P Navarria2 1Neurosurgery Department, Radiotherapy Unit, Fondazione IRCCS Istituto Neurologico C. Besta, Milan, Italy; 2Radiotherapy and Radiosurgery Department, Humanitas Cancer Center and Research Hospital, Rozzano, Milan, ItalyCorrespondence: V PinziNeurosurgery Department, Radiotherapy Unit, Fondazione IRCCS Istituto Neurologico C. Besta, Via G. Celoria 11, Milan 20131, ItalyTel +390223942312Email valentinapinzi@yahoo.itAbstract: Treatment options for intracranial meningiomas are surgical resection alone, surgery followed by adjuvant radiation therapy (RT), or exclusive RT. Parasagittal and parafalcine meningiomas are a subgroup of meningeal disease located close to the vascular structures. Considering the frequent venous invasion, a complete resection is not possible in the majority of cases, and even if a Simpson Grade I resection can be performed, the risk of recurrence is relevant. To date, few studies are focused on parasagittal and parafalcine meningiomas. Because of their specific related issues, particular considerations on decision-making process, outcome, and toxicity follow-up are mandatory. In fact, parasagittal and parafalcine meningiomas require a clear-cut radiological assessment, as well as a tailored toxicity risk evaluation. Moreover, similarly to other meningioma sites, also for parasagittal and parafalcine ones, a standardization of local control, toxicity, and quality of life evaluation is needed in order to lead to a pooled analysis of the results. In this context, our aim was to review the literature data regarding the role of both single-session and multisession radiosurgery (RS), and stereotactic radiotherapy (SRT) for parasagittal and parafalcine meningioma management, summarizing available data on safety and efficacy. It was also discussed how RS and SRT can be performed in a setting of evolving views concerning the treatment paradigm of the parasagittal and parafalcine meningiomas.Keywords: meningioma, parasagittal meningioma, parafalcine meningioma, stereotactic radiotherapy, radiosurgery, radiotherapy